Novel insights into contact dermatitis - Johansen, Jeanne Duus; Bonefeld, Charlotte Menné; Schwensen, Jakob Ferløv Baselius; Thyssen, Jacob Pontoppidan; Uter, Wolfgang (Journal of Allergy and Clinical Immunology, 2022)
Contact dermatitis is a common disease that is caused by repeated skin contact with contact allergens or irritants, resulting in allergic contact dermatitis (ACD) and/or irritant contact dermatitis. Attempts have been made to identify biomarkers to distinguish irritant and allergic patch test reactions, which could aid diagnosis. Some promising candidates have recently been identified, but verification and validation in clinical cases still need to be done. New causes of ACD are constantly being recognized. In this review, 10 new contact allergens from recent years, several relating to anti-aging products, have been identified. Frequent allergens causing considerable morbidity in the population, such as the preservative methylisothiazolinone, have been regulated in the European Union. A significant drop in the number of cases has been seen, whereas high rates are still occurring in other areas such as North America. Other frequent causes are fragrance allergens, especially the widely used terpenes and acrylates found in medical devices for control of diabetes. These represent unsolved problems. Recent advances in immunology have opened the way for a better understanding of the complexity of contact dermatitis, especially ACD—a disease that may be more heterogenous that previous understood, with several subtypes. With the rapidly evolving molecular understanding of ACD, the potential for development of new drugs for personalized treatment of contact dermatitis is considerable.
CRIS-Team Scopus Importer:2022-04-29
Keywords: Allergic contact dermatitis; CXCL10; CXCL9; dupilumab; epidermal transcriptome; IL-16; innate immunity; irritant contact dermatitis; isobornyl acrylate; JAK-1 inhibitor; methylisothiazolinone; T; ZBP1